Web engineering for workflow-based applications: models, systems and methodologies - Freudenstein, Patrick (KIT Scientific Publishing, 2009)
Workflow-based Web applications present a central pillar of companies' endeavors towards increased business process efficiency and flexibility. Considering their particular characteristics, this book presents innovative approaches for their efficient, completely model-driven construction with particular emphasis on effective stakeholder involvement, usability-oriented dialog design and cross-methodological reuse.